Exposure to air pollution in England, 2003-23 - Lucie Gadenne; Marion Leroutier; Rodrigo Toneto; Bobbie Upton (Institute for Fiscal Studies (IFS), 2024)
We set out how air pollution (PM2.5) has changed across England and explore inequalities by ethnicity, income deprivation, region and age.
Keywords: 330; Health and social care; Poverty; inequality and social mobility; Environment; Geography; Health; Inequality; Race